Technical and economic study of different mechanized operations in the coffee culture - Cunha, Joao Paulo Barreto; da Silva, Fabio Moreira; Lorenzoni Martins, Felipe Gabriel; da Conceição, Fagner Goes; Camelo, Lais Guerra (Coffee Science - ISSN 1984-3909, 2016)
After the adoption of mechanization in coffee growing many formerly manual operations are now performed by machines, allowed increased production capacity and reduce costs. The knowledge and application of technical and economic criteria for obtaining production costs are of paramount importance as they allow the estimated costs show strength and are reliable, providing better market competitiveness. With the objective of conduct a technical and economic analysis of different mechanized operations in coffee the work was carried out in Alfenas- MG, which assessed the time required to perform various operations mechanized sets and also their respective fixed and variable costs were analyzed. The analysis of each set was performed by the product of total hours spent in each operation, in terms of production costs. Based on data obtained times of repairs and maintenance directly affect the mechanical availability of mechanized sets. The depreciation and fuel costs are the main components that make up the fixed and variable costs, respectively. The coffee gathering and sweeping operations are the worst technical feasibility and hence economical, featuring superior unproductive costs to production costs.